KONSTRUKSI PROFIT SHARING DALAM BISNIS SYARIAH - Mardhiyah Hayati (Khatulistiwa, 2012)
Specifically, there is a popular musyarakah form; it’s mudharabah. The mudharabah is a cooperation between a capital owner and an entrepreneur who has skill or power in running a project. With mudhārabah, two persons who have cooperation do not get money lending interest, but they will get profit sharing from a project agreement. In mudharabah, one provides the capital, and the other runs it with effort through management. The first party is called a shahib al-mal (financier), and the second party is called a mudharib (entrepreneur). So, in mudharabah transaction scheme, capital is 100 % from shahib al-mal (financier), and the management is done by a mudharib (entrepreneur).